Application of the Project Based Learning Model to Increase Student Activity and Student Learning Outcomes in Basic Computer and Network Subjects - hasan, ibnu (Jurnal Guru Komputer, 2022)
The research aims to increase student activity and motivation in the subject of Computers and Basic Networks in class X TKI SMK Negeri 2 Bandung by using the Project Based Learning model. This research is Classroom Action Research (CAR) which aims to overcome existing problems in class. The research subjects were class X TKI students in the even semester of the 2019/2020 academic year, a total of 35 students. The research was conducted in two cycles and at the end of each cycle a reflection was made on the actions given. Data collection techniques in research is using observation sheets, questionnaires, and documentation. The results show that the implementation of learning using the Project Based Learning model in the Basic Computer and Networks subject can increase student activity and motivation. The result show that student activeness went from of 71.84% in Cycle 1 increased in Cycle 2 with 74.61%, and student completion rate went from of 78% in Cycle 1 to 100% in Cycle 2. It is proved that the Project Based Learning model can increase student activity in Basic Computer and Network Subjects.